Inflammation-Induced Adverse Pregnancy and Neonatal Outcomes Can Be Improved by the Immunomodulatory Peptide Exendin-4 - Garcia-Flores, Valeria; Romero, Roberto; Miller, Derek; Xu, Yi; Done, Bogdan; Veerapaneni, Chharitha; Leng, Yaozhu; Arenas-Hernandez, Marcia; Khan, Nabila; Panaitescu, Bogdan; Hassan, Sonia S.; Alvarez-Salas, Luis Marat; et al. (Frontiers in Immunology, 2018)
Preterm birth is the leading cause of neonatal morbidity and mortality worldwide. Inflammation is causally linked to preterm birth; therefore, finding an intervention that dampens maternal and fetal inflammatory responses may provide a new strategy to prevent adverse pregnancy and neonatal outcomes. Using animal models of systemic maternal inflammation (intraperitoneal injection of lipopolysaccharide) and fetal inflammation (intra-amniotic administration of lipopolysaccharide), we found that: 1) systemic inflammation induced adverse pregnancy and neonatal outcomes by causing a severe maternal cytokine storm and a mild fetal cytokine response; 2) fetal inflammation induced adverse pregnancy and neonatal outcomes by causing a mild maternal cytokine response and a severe fetal cytokine storm; 3) exendin-4 treatment of dams with systemic inflammation or fetal inflammation improved adverse pregnancy outcomes by modestly reducing the rate of preterm birth; 4) exendin-4 treatment of dams with systemic, but not local, inflammation considerably improved neonatal outcomes, and such neonates continued to thrive; 5) systemic inflammation facilitated the diffusion of exendin-4 through the uterus and the maternal-fetal interface; 6) neonates born to exendin-4-treated dams with systemic inflammation displayed a similar cytokine profile to healthy control neonates; and 7) treatment with exendin-4 had immunomodulatory effects by inducing an M2 macrophage polarization and increasing anti-inflammatory neutrophils, as well as suppressing the expansion of CD8+ regulatory T cells, in neonates born to dams with systemic inflammation. Collectively, these results provide evidence that dampening maternal systemic inflammation through novel interventions, such as exendin-4, can improve the quality of life for neonates born to women with this clinical condition.